2022
DOI: 10.1371/journal.pone.0269448
|View full text |Cite
|
Sign up to set email alerts
|

The relative role of executive control and personality traits in grit

Abstract: Although grit is predictive of wellbeing, educational achievement, and success in life, it has been conceptualized as largely distinct from cognitive ability. The present study investigated the link between grit and executive functions since regulation abilities might underlie the expression of grit. A hundred thirty-four people were administered personality questionnaires (grit, impulsiveness, and mindfulness) and four experimental tasks tapping into Miyake’s and Braver’s models of executive functioning (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Eskreis-Winkler et al (2016) reported that grit and cognitive ability do not correlate with several studies. In connection to this, a more recent study conducted by Aguerre et al (2022) among 134 participants highlighted that higher grit scores did not correlate to higher overall cognitive ability. Despite this, they signified that higher grit scores were significantly related to higher levels of mindfulness and lower impulsivity, both factors highly associated with self-regulation.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Eskreis-Winkler et al (2016) reported that grit and cognitive ability do not correlate with several studies. In connection to this, a more recent study conducted by Aguerre et al (2022) among 134 participants highlighted that higher grit scores did not correlate to higher overall cognitive ability. Despite this, they signified that higher grit scores were significantly related to higher levels of mindfulness and lower impulsivity, both factors highly associated with self-regulation.…”
Section: Introductionmentioning
confidence: 88%
“…These findings were parallel to the suggestions of Duckworth and Quinn (2009), which signified that people with high grit rely more on whatever kind of capacity they have rather than having a higher cognitive ability. Aguerre et al (2022) argued that future research should comprehensively evaluate grit and other fluid intelligence variables. Fluid intelligence pertains to one's ability to solve problems and reason without existing knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred twenty people (Mage = 23.11, SDage = 4.19, Range = 18-33, 69% female) completed the study in exchange for course credits (0.1credit/40 min) or monetary reward (7€/1 h). This sample took part in a larger individual differences study from which other non-overlapping findings have been already reported (Aguerre et al, 2020(Aguerre et al, , 2021(Aguerre et al, , 2022. To confirm that the sample size of the bigger project was enough to capture the desired effects, we calculated a priori power analysis (G*Power 3.1.9.2; Erdfelder et al, 1996) based on the effect of the linear regression reported by Kong et al (2016), with an R 2 = .14, as we also adopted an regression approach.…”
Section: Methods Participantsmentioning
confidence: 99%